Privacy Preserving for Cloud Computing Using Cryptography in Big Data: A Review - Kumari, Anjali; Namdeo, Varsha (International Journal of Computer Sciences and Engineering, 2019)
Now a days Cloud computing services highly demanded in all over the world due to its large size spaces for data storing. Cloud Computing provides the ability to utilize resources through Internet. As a lot of service providers of the cloud are available in the competitive computer world. Security in Cloud computing is an important and critical aspect, and has numerous issues and problem related to it. In this paper we will survey of previous author’s research that how they analyses approaches for secure data from the unauthorized users and provide integrity to the users. It requires a very high degree of privacy and authentication. To protect the data in cloud database server, cryptography is one of the important techniques for the security purposes. Cryptography provides various symmetric and asymmetric algorithms to secure the data.